EFFECT OF PULSATLITY IN CENTRAL AORTA ON CEREBRAL BLOOD FLOW WITH ADVANCING AGE AND HYPERTENSION. (June 2018) - Kim, M.; Tan, I.; Butlin, M.; Avolio, A.
Abstract: Objective: Increasing pulsatility in the central aorta with arterial stiffening has been suggested as a potential causative factor of age-related cerebral dysfunction associated with cognitive impairment and cerebral small vessel disease. We recently showed in a large cohort (n = 1020) that changes of pulsatile features of the central aortic pressure (cAP) waveform (eg. increase of late systolic secondary augmented pressure) with advancing age are related to corresponding pulsatile features of flow velocity (FV) in cerebral arteries. The aim of this current study was to assess the association of pulsatility of central aortic pressure (cAP) and cerebral arterial FV with age and hypertension. Design and method: Three groups of adult subjects were studied: normotensive (NT; n = 22, age 28 ± 4.8 yrs); young hypertensive (YHT; n = 11, age 41 ± 5.4 yrs) and old hypertensive (OHT; n = 12, age 63 ± 6.2 yrs). Hypertension was defined as brachial systolic pressure >140 mmHg or diastolic pressure >90 mmHg. Non-invasive measurements of cAP were obtained from transformation of calibrated radial tonometry waveforms (SphygmoCor, AtCor Medical, Sydney). Cerebral FV was recorded by a transcranial Doppler device in the middle cerebral artery. Pulsatility index) was computed as the ratio of pulse to mean components of cAP (pPI) and cerebral FV (fPI). Results: There was a significant difference in mean arterial pressure in YHT (108.5 ± 6.1 mmHg) and OHT (111.7 ± 11.8 mmHg) compared to the NT (87.2 ± 6.6 mmHg, p < 0.05). The associated pules pressure (mmHg) was NT:41 ± 9; YHT:56 ± 6; OHT:84 ± 34). There were no significant corresponding changes in mean FV (NT:61.1 ± 11.9 cm/s; YHT:67.2 ± 17.3 cm/s; OHT:59.6 ± 20.5 cm/s). Compared to NT, corresponding mean changes (%) of pPI and fPI were YHT: pPI = 19% (p < 0.05), fPI = 16% (NS); OHT:pPI = 85% (p < 0.05), fPI = 46% (p < 0.05). Conclusions: Findings show that mean cerebral flow at rest is maintained with changes in mean systemic arterial pressure in young and old hypertensive subjects due to cerebral autoregulation. With hypertension, cerebral flow pulsatility increases with age, likely due to increased stiffness of systemic arteries. Increased pulsatility in the presence of cerebral autoregulation suggests greater exposure of resistive cerebral vasculature to deleterious effects of cyclic mechanic stress.